2017
DOI: 10.1021/acsomega.7b00547
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Nondegradable Si@SiOx/n-Carbon Crystallite Composite Anode for Lithium-Ion Batteries

Abstract: A Si-based anode maintaining its high electrochemical performance with cycles was prepared for the nondegradable lithium-ion battery. Nanoscaled Si particles were mechanochemically coupled with approximately 3 nm thick oxide layer and n-carbon (nanoscaled carbon) crystallites to overcome silicon’s inherent problems of poor electronic conductivity and severe volume change during lithiation and delithiation cycling. The oxide layer of SiO x was chemically formed via a controlled oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…44,45 In addition, compared with the characteristic peak of commercial Si at 521.9 cm −1 , the HM-Si/SiO x nanoboxes exhibit a weak and slightly blue-shift peak at around 509.8 cm −1 , probably related to the strong optical phonon mode of Si nanodots confined in the SiO x matrix. 46 This result verifies the high crystallinity of Si nanocrystals within the heterostructures. Note that the Si band of HM-Si/SiO x nanoboxes becomes sharper, and this is mainly generated by the excessive consumption of silica, resulting in the exposure of internal Si nanocrystals.…”
Section: Resultssupporting
confidence: 63%
“…44,45 In addition, compared with the characteristic peak of commercial Si at 521.9 cm −1 , the HM-Si/SiO x nanoboxes exhibit a weak and slightly blue-shift peak at around 509.8 cm −1 , probably related to the strong optical phonon mode of Si nanodots confined in the SiO x matrix. 46 This result verifies the high crystallinity of Si nanocrystals within the heterostructures. Note that the Si band of HM-Si/SiO x nanoboxes becomes sharper, and this is mainly generated by the excessive consumption of silica, resulting in the exposure of internal Si nanocrystals.…”
Section: Resultssupporting
confidence: 63%
“…It was reported that the SiO x morphology was well retained during charge/discharge process because of existence of non-active SiO 2 buffer matrix that could prevent severe volume expansion arising from Li-Si alloying reaction. 8,38 Thus, it was supposed that the SEI formed after the PLSC process might keep its original shape despite charge/discharge process of SiO x , which implies that the initial formation of SEI by the PLSC process might determine the electrochemical performances of the SiO x electrode. (Supporting Figure S6) However, after 12 hours of the PLSC process, too much SEI was stacked at the electrode, and then SEI cracked with formation of many boundaries at the electrode, which indicates the negative effect of excessive PLSC processing.…”
Section: Resultsmentioning
confidence: 99%
“…Because the gravimetric energy density of graphite-based energy materials typically used as anodes in LIBs is only ∼372 mAh g −1 , the development of novel high-energy-density electrode materials is needed for further grid-scale application of LIBs. [4][5][6][7] However, most potential high-energy-density anode materials for LIBs, such as Si, 8,9 SnO 2 , 10,11 Co 3 O 4 , 12,13 and other materials, 14,15 are based on a conversion or alloying reaction, which is accompanied by large volume change during charge/discharge. This large volume change results in poor cycle life due to pulverization of the anode materials and unwanted continuous formation of a solid-electrolyte interphase (SEI) that reduce the stable cycle life.…”
mentioning
confidence: 99%
“…Figure 13 compares a representative Raman spectrum obtained for field VI-D (L S = 25 nm, D S = 1.2 × 10 6 ions/spot) to several reference spectra of amorphous SiC and SiOC grown and thermally treated under different conditions [51][52][53][54][55]. While the spectra appear related, the agreement is only qualitative; possibly a substance mixture is present.…”
Section: Chemical Inferences: Reactions With Mobile O Si and C Atomsmentioning
confidence: 97%